Unsupervised change detection in SAR images based on Gauss log ratio image fusion NSCT analysis and compressed projection - A, Aneesa Fathima; Sunny, Liya Elizabeth (IJRDO -Journal of Computer Science Engineering, 2015)
Multitemporal synthetic aperture radar (SAR)images helps in detecting different types of terrain changes.Due to the presence of speckle noise and complex terraindetecting the changes in SAR images has become a complextask. In this paper an unsupervised method for detecting thechanges in SAR images has been proposed. First Gauss logoperator and log operator are applied on the SAR images toobtain the difference image. Image fusion and then image denoising is performed on the difference image using Nonsubsampled counter let transform (NSCT).Compressedprojection is performed to extract the feature vectors. Finallythe feature vectors are partitioned by using Fuzzy clusteringapproach into two classes, changed class and unchanged class.